Exploring perceptions, readiness, barriers, and facilitators related to the potential implementation of postpartum depression screening: A mixed-methods study in a Lebanese maternity setting - Lama El Haj Sleiman; Linda Abou-Abbas (PLoS ONE, 2026)
Background Postpartum depression (PPD) is a common mental health condition affecting mothers, infants, and families, with higher prevalence in middle-income countries. Despite its burden, PPD remains under-screened in Lebanese public hospitals, particularly in disadvantaged areas like Tripoli. Objectives To assess nurses’ knowledge, attitudes, and practices regarding PPD and explore facilitators, and barriers influencing the potential implementation of systematic PPD screening. Methods A mixed-methods study was conducted in a Lebanese public university hospital, combining a quantitative survey with qualitative focus group discussions involving nurses and managers. Descriptive analyses were applied to survey data, and thematic analysis was used for qualitative findings. Results Most nurses were aware of PPD (92.9%) and “baby blues” (92.9%), but only 21.4% were aware of standardized screening tools. Correct identification of key symptoms was reported by 71.4%, while only 35.7% correctly identified all risk factors and 28.6% recognized appropriate combined management (psychotherapy and antidepressants). Regarding attitudes, all participants (100%) agreed that PPD screening should be part of routine postnatal care, and 92.9% recognized its seriousness and the role of nurses in early detection. However, only 78.6% felt confident identifying PPD signs. In terms of practice, only 28.6% consistently assessed mothers’ emotional well-being before discharge. Qualitative findings suggested a generally positive attitude toward the potential implementation of screening, while also highlighting perceived barriers, including insufficient training, unclear role delineation, inadequate referral pathways, time constraints, and weak internal communication regarding mental health services. Conclusion The findings suggest that challenges to the potential implementation of PPD screening may be related to capacity and organizational support than to resistance among participants. Strengthening training, integrating standardized screening into routine postnatal care, clarifying roles and referral pathways may facilitate the implementation of PPD screening. Given the exploratory nature of this single-center study, further research is needed to assess the transferability of these findings to other maternity care settings in Lebanon.